Ultrabroadband Photonic Structures To Achieve High-Performance Daytime Radiative Cooling - Rephaeli, Eden; Raman, Aaswath; Fan, Shanhui (Nano letters, 2013)
If properly designed, terrestrial structures can passively cool themselves through radiative emission of heat to outer space. For the first time, we present a metal-dielectric photonic structure capable of radiative cooling in daytime outdoor conditions. The structure behaves as a broadband mirror for solar light, while simultaneously emitting strongly in the mid-IR within the atmospheric transparency window, achieving a net cooling power in excess of 100 W/m2 at ambient temperature. This cooling persists in the presence of significant convective/conductive heat exchange and nonideal atmospheric conditions.